Environmental Knowledge and Awareness as a Key Driver of Green City Strategy: A Case Study of Malang City - Galang Fairuz Reksa Ashfahani; Moh. Khusaini; Bunga Hidayati (Postgraduate, University of Mataram, 2025)
This study aims to analyze the institutional and government readiness and identify the strengths, weaknesses, opportunities, and threats along with strategies to realize a green city in Malang City. Qualitative research methods in the form of SWOT analysis were used by involving informants from the State Civil Apparatus at the Regional Development Planning Agency and the Environmental Service of Malang City. The results of the study indicate that the institutional in Malang City is still weak, marked by the absence of a multidisciplinary working group for a green city. In addition, government readiness is still low due to lack of concern, a conventional